El método dialógico: una experiencia interdisciplinaria desde la antropología - Muñoz, Jonathan (2013)
Dialogic method is born from the interdisciplinary application of the Mijail Bajtin’s “reading in depth”, method with which this language philosopher analyzed literary works. This experience has sprung from anthropology, in conjunction with history and geography, in a thesis developed in Paso Canoas, binational community of Costa Rica and Panama.